A inteligência artificial no contexto das ciências cognitivas - Lira, Tércio Onofre de (2011)
Currently there is a wide range of applications in Artificial Intelligence, but progress goes in short steps regarding the development of a strong artificial intelligence. This thesis aims to elucidate the multidisciplinary character of cognitive science to which the studies of artificial intelligence are linked. The objective is to describe succinctly, but panoramically, the history of each area such as cognitive neuroscience, philosophy of mind, cognitive psychology, artificial intelligence, among others) as well as to describe the main questions and barriers of actual researches. The major effort of this project is to make explicit the state of the art of artificial intelligence focusing on the goals of cognitive science towards strong artificial intelligence. Therefore, this dissertation includes a bibliography of evolutionary concepts, and the role of the various disciplines involved in current developments of strong artificial intelligence. It will also highlight the great contribution that is being given in cognitive sciences to the study of cognitive semiotics. As much as the area is evolving, it is noted the need for a new doctrine to develop an "artificial being". Algorithmic issues, new architectural arrangements of machine and interpretations of signs / symbols could be useful to achieve this goal